2020
DOI: 10.1515/cclm-2019-1104
|View full text |Cite
|
Sign up to set email alerts
|

An international multi-center serum protein electrophoresis accuracy and M-protein isotyping study. Part I: factors impacting limit of quantitation of serum protein electrophoresis

Abstract: BackgroundSerum protein electrophoresis (SPEP) is used to quantify the serum monoclonal component or M-protein, for diagnosis and monitoring of monoclonal gammopathies. Significant imprecision and inaccuracy pose challenges in reporting small M-proteins. Using therapeutic monoclonal antibody-spiked sera and a pooled beta-migrating M-protein, we aimed to assess SPEP limitations and variability across 16 laboratories in three continents.MethodsSera with normal, hypo- or hypergammaglobulinemia were spiked with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 18 publications
2
17
0
2
Order By: Relevance
“…The serum IFE assessed migration patterns for γ, α, μ, κ, and λ immunoglobulin chains (Hydrasys and Hydragel; Sebia) with a sensitivity of approximately 0.5 g/L 10,11 . Urine IFE assays were performed on the same day as receipt of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The serum IFE assessed migration patterns for γ, α, μ, κ, and λ immunoglobulin chains (Hydrasys and Hydragel; Sebia) with a sensitivity of approximately 0.5 g/L 10,11 . Urine IFE assays were performed on the same day as receipt of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have compared gel to capillary electrophoresis [ 8 , [13] , [14] , [15] ] and shown excellent agreement (>95%) in determining the concentration of the five serum protein fractions (albumin, alpha-1, alpha-2, beta, and gamma). Goal of the present study was to compare the performance of gel electrophoresis to that of the new capillary electrophoresis apparatus Capillarys III Tera (Sebia, Lisses, France) in a routine clinical setting at a tertiary referral hospital, using a large patient population and focusing on the characterization of the M-spike.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormality of monoclonal protein may be the alert for undercovered lymphoid malignancy or other pathologic complications [3]. The monoclonal protein serves as a tumor (or clonal) marker in these patients and needs to be monitored to determine whether the clone of plasma cells is expanding [4,5]. The role in the diagnosis, classification, and management of this disorder is committed by quantifying and immunotyping of serum proteins.…”
Section: Introductionmentioning
confidence: 99%